Human dignity, fundamental rights and administrative law - Bacellar Filho, Romeu Felipe (Universidad Nacional del Litoral, 2014)
Fundamental rights and human dignity took over, in the Constitutional State of law courts, a prominent role in the context of Administrative Law. This essay aims to analyze the intrinsic relations that these topics feature in the present days, emphasizing the importance of dealing with the Public Administration from the perspective of the citizen and human rights protection.